2007
DOI: 10.1017/s0025315407053702
|View full text |Cite
|
Sign up to set email alerts
|

Localized field effects of drainage water from abandoned coal mines on intertidal rocky shore seaweeds at St Monans, Scotland

Abstract: This is the first account of the effects of drainage water from an abandoned coal mine on the seaweed community of the intertidal rocky shore in the British Isles. At St Monans, Scotland, along a 250 m transect, the brown climax species Fucus spiralis showed a low abundance in sampling quadrats (17.5%) and small plant size (3.5 cm), close to the outfall, compared to stations at increasing distance from the drainage source. Immediately below the outfall the fucoid community was replaced by a mixture of 12 speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…There is a remarkable resemblance between seaweed community features on the shores here described and those described by Woolsey and Wilkinson (2007), on a shore affected by acid mine drainage in the UK. Seaweeds collected under such different scenarios exhibit similar increased metal accumulation (Woolsey and Wilkinson 2007;Wallenstein et al 2009;Wallenstein 2011). In both studies, intertidal communities are affected by acidic, metal-enriched, freshwater inputs (Carvalho et al 2011;Woolsey and Wilkinson 2007).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…There is a remarkable resemblance between seaweed community features on the shores here described and those described by Woolsey and Wilkinson (2007), on a shore affected by acid mine drainage in the UK. Seaweeds collected under such different scenarios exhibit similar increased metal accumulation (Woolsey and Wilkinson 2007;Wallenstein et al 2009;Wallenstein 2011). In both studies, intertidal communities are affected by acidic, metal-enriched, freshwater inputs (Carvalho et al 2011;Woolsey and Wilkinson 2007).…”
Section: Discussionsupporting
confidence: 63%
“…Such evidence is a direct result of the destructive effect of pH on the calcareous skeleton of coralline algae as shown by Couto et al (2010), Jokiel et al (2008) and Martin and Gattuso (2009). There is a remarkable resemblance between seaweed community features on the shores here described and those described by Woolsey and Wilkinson (2007), on a shore affected by acid mine drainage in the UK. Seaweeds collected under such different scenarios exhibit similar increased metal accumulation (Woolsey and Wilkinson 2007;Wallenstein et al 2009;Wallenstein 2011).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Seasonal variation in the copper content of coastal seawater was measured (Atkins, 1953) and probably reflected periods of increased river flow. Drainage waters from coal mines were also shown to have adverse effects on estuarine fauna (Woolsey & Wilkinson, 2007).…”
Section: Heavy Metal Pollutionmentioning
confidence: 99%
“…In streams receiving discharge from an active tungsten mine in central Portugal, larval growth and development were highly inhibited compared to a decrease in the inhibition of larval growth in streams near an abandoned gold mine that had been undergoing rehabilitation.Toxicity to Plants. Another way to assess the toxicity of mine drainage is to study the effects of drainage water on aquatic plants Woolsey and Wilkinson (2007). examined the seaweed community at St. Monans, Scotland, near an abandoned coal mine, and found that the seaweed Fucus spiralis showed a low abundance in sampling quadrats and small plant size close to the outfall compared to stations farther away from the drainage source.…”
mentioning
confidence: 99%